Flow photochemical Giese reaction via silane-mediated activation of alkyl bromides. (6th March 2023) - Fanini, Fabiola; Luridiana, Alberto; Mazzarella, Daniele; Alfano, Antonella Ilenia; van der Heide, Perry; Rincón, Juan A.; García-Losada, Pablo; Mateos, Carlos; Frederick, Michael O.; Nuño, Manuel; Noël, Timothy
Graphical abstract: Abstract: Organic halides play a key role as building blocks in synthesis because of their low cost and wide availability. In recent years, halogen-atom transfer (XAT) has emerged as a reliable approach to exploit these substrates in radical processes. Herein, we report a hydroalkylation of electron-poor olefins using alkyl bromides based on a UVA-induced silane-mediated XAT reaction. Our protocol is operationally simple, displays a broad scope and does not require a photocatalyst. Flow technology was used to reduce the reaction times and scale the process. Notably, a two-step protocol, combining the XAT protocol with a subsequent Horner-Wadsworth-Emmons reaction, has been developed to enable the allylation of C(sp 3 )–Br bonds.